THE RELATIONSHIP BETWEEN INTEREST IN FOLLOWING ONLINE LEARNING WITH LEARNING OUTCOMES IN BASIC BOGA SUBJECTS DEPARTMENT OF CULINARY ADMINISTRATION IN VOCATIONAL HIGH SCHOOLS - Suhairi, Laili; Maryam, Siti; Kinara, Humaira; Faudiah, Nurul; Gagarin, Yuri (IJBLE Scientific Publications Community Inc., 2023)
At the beginning of 2020, education in Indonesia implemented online learning to prevent the spread of Corona Virus Disease (COVID-19). Students who take part in online learning have an increasingly high interest in learning, and there are also students who, since online learning is carried out, have less interest in learning. The research aims to find out students' interest in participating in online learning with learning outcomes that are held in the Basic Culinary Subject of the Culinary Department Odd Semester Academic Year 2020/2021. Quantitative descriptive research approach, sampling with saturated sample technique. Respondents totaled 37 people, namely class XI students who took Basic Culinary Subjects. Questionnaire data collection techniques, observation, documentation, and report cards. Descriptive data analysis and prerequisite test or normality test and linearity test. The study found a positive relationship between interest in online learning and learning outcomes in Basic Culinary Subjects, with a Pearson correlation value of 0.155 significance level of 0.498 > 0.05. This means that there is no correlation between interest in participating in online learning and student learning outcomes in basic culinary subjects in the culinary department at SMK Negeri 1 Takengon. It was concluded that the relationship between interest in online learning and student learning outcomes in the Basic Culinary Subject of the Culinary Department for the 2020/2021 Academic Year is weak.